Intestinal Microbial Composition of Children in a Randomized Controlled Trial of Probiotics to Treat Acute Gastroenteritis - Rachael G. Horne; Stephen B. Freedman; Kathene C. Johnson-Henry; Xiao-Li Pang; Bonita E. Lee; Ken J. Farion; Serge Gouin; Suzanne Schuh; Naveen Poonai; Katrina F. Hurley; Yaron Finkelstein; Jianling Xie; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Compositional analysis of the intestinal microbiome in pre-schoolers is understudied. Effects of probiotics on the gut microbiota were evaluated in children under 4-years-old presenting to an emergency department with acute gastroenteritis. Included were 70 study participants (n=32 placebo, n=38 probiotics) with stool specimens at baseline (day 0), day 5, and after a washout period (day 28). Microbiota composition and deduced functions were profiled using 16S ribosomal RNA sequencing and predictive metagenomics, respectively. Probiotics were detected at day 5 of administration but otherwise had no discernable effects, whereas detection of bacterial infection (P<0.001) and participant age (P<0.001) had the largest effects on microbiota composition, microbial diversity, and deduced bacterial functions. Participants under 1 year had lower bacterial diversity than older aged pre-schoolers; compositional changes of individual bacterial taxa were associated with maturation of the gut microbiota. Advances in age were associated with differences in gut microbiota composition and deduced microbial functions, which have the potential to impact health later in life.Clinical Trial Registrationwww.ClinicalTrials.gov, identifier: NCT01853124.